Design of compact microstrip bandpass filter using square DMS slots for Wi-Fi and bluetooth applications - A. Belmajdoub; M. Jorio; S. Bennani; A. Lakhssassi; M. Amzi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
This paper presents the design of a compact bandpass filter based on two identical rectangular resonators and is implemented on microstrip technology for Wi-Fi and bluetoothapplications. To reduce the size of the filter, the defected microstrip structure (DMS) technique is proposed. This technique consists of etching slots in the rectangular resonator, which results in a change in the line properties and increase of the effective inductance and capacitance. This feature is used for miniaturization. The designed filter has a compact size (6.82x8.3) mm² with a low insertion loss of -0.1 dB and a good return loss of -36 dB. The simulation results are realized using the (computer simulation technology) CST Microwave software.